Zavarovanje odgovornosti v prometu - za zaščito potnikov in prevoznikov - Veberič, Jernej (Podjetje in delo, 2015)
It has been a long time since we could imagine our lives without traffic with motor means of transport. In spite of all the benefits, such means of transport can be extremely dangerous. A short moment of inattention or an imperceptible technical error can cause a disastrous accident with tragic consequences. Users of such means of transport - passengers - have to have an adequate legal protection for such occurrences. Law of damages provides strict measures of carrier (as owner of the means of transport) liability and sets boundaries of indemnity rights of passengers. The liability insurance contract, concluded by the carrier, however, enables two things: it makes it easier for the passenger as a third party to receive indemnity, because the indemnity is paid out by the insurance company; to the carrier, on the other side, it enables a normal, continuous operation, because the indemnity is not paid out of their own funds. Indemnity and insurance legal bases vary among different means of transport in different countries. National, European and other international regulations are interwoven - but not always consistent with each other. This is what makes a discussion of this matter even more varied and interesting.
Keywords: cestni promet; javni prevoz; odškodninska odgovornost; potniki; transportno pravo; zavarovanje